This ability over disability talents on the spectrum : a series of music workshops designed and implemented for children with Autism Spectrum Disorder (ASD) in Batino Elementary School - SPED Center - Torres, Samantha Andre
The project will be composed of a series of musical workshops for elementary students with special needs. The participants would be individuals with Autism Spectrum Disorder (ASD). Aside from the development and learning of specific musical skills, the project aims to use music as an avenue for expression thus leading to observable behavioral changes. The project will run for 6 months in the SPED Center of Batino Elementary School in Quezon City.